Changing social care : a handbook for managers - Kelly, Des, 1952- (Whiting and Birch Ltd., 1996)
Changing Social Care addresses the changing political context within which social care managers operate and assesses the impact on their work of new trends in service delivery. It suggests that they need to pay attention not only to the context but also the content and process of change. Change implementation focuses on the key dimensions of strategy, structure, culture and people. These dimensions are explored through case studies. Building commitment to change is stressed throughout.